Decentralised Planning and Poverty Reduction: the Case of Kerala. - Balan, P.P (2006)
Despite over five decades of rapid economic growth and poverty alleviation programmes, around 350 million persons in India are considered to be below poverty line. The current scenario calls for a closer examination of the pitfalls in the centralized planning process with regard to poverty reduction. For surmounting the turbulence in the process of development, social protection is required for underprivileged and marginalized groups. At the same time social protection cannot be divorced from economic and social policies affecting the rate and distribution of economic growth and human capital formation. Developing a good local governance system is one of the strategies of India for sustainable human development. Kerala legislated the Kerala Panchayati Raj Act 1994 (for local bodies in rural areas) and the Kerala Municipality Act 1994 (for the local bodies in urban areas), and transferred powers, functions and finance to these local bodies to act as institutions of self-governance. The objective of this paper is to provide background information for reflecting on some alternatives for the development of the poor and marginalized groups within the framework of experience of Kerala.